A Systematic Review of Impulse Buying Behavior in Generation Z: Drivers, Channels, and Psychological Triggers - Ramadhani Azka, Shafira; Mulia Wibawa, Berto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
To synthesize evidence on internal and external drivers, digital channels, and psychological triggers that shape online impulse buying among Generation Z across social media and e-commerce ecosystems, integrating the Stimulus–Organism–Response perspective with self-control. A systematic literature review of Scopus-indexed records was conducted using a predefined Boolean query aligned with PRISMA guidelines. Fifty five studies published between 2018 and 2025 were included after multi stage screening and full-text appraisal. Data were coded through descriptive and thematic analysis to capture internal external drivers, channels, and psychological mechanisms. The review highlights three regularities. First, internal drivers include hedonic motives, affective states, novelty seeking, and lapses in self-control, with boredom, stress, and anxiety operating as situational triggers. Second, external drivers encompass discounts, scarcity, interactivity, gamification, service quality, and payment design, with buy-now-pay-later and e-wallets reducing the pain of paying while cash-on-delivery enhances control. Third, digital channels most conducive to impulsivity are TikTok and TikTok Shop, Shopee, live commerce formats, sponsored ads, and personalized mobile apps. Psychological triggers cluster into social comparison and FOMO, affective instability, and reward seeking, showing that Gen Z’s impulsivity is largely affect-driven, socially amplified, and reward-oriented. By consolidating 55 studies, this review provides the most comprehensive framework to date linking drivers, channels, and triggers for Gen Z impulse buying, addressing prior fragmentation. The findings call for responsible promotions, transparent scarcity signals, ethical personalization, and stronger financial literacy initiatives to balance commercial innovation with consumer protection.